On‐Deck Seismology: Lessons from InSight for Future Planetary Seismology. Issue 4 (18th April 2020) - Panning, M. P.; Pike, W. T.; Lognonné, P.; Banerdt, W. B.; Murdoch, N.; Banfield, D.; Charalambous, C.; Kedar, S.; Lorenz, R. D.; Marusiak, A. G.; McClean, J. B.; Nunn, C.; et al.
Abstract: Before deploying to the surface of Mars, the short‐period (SP) seismometer of the InSight mission operated on deck for a total of 48 hr. This data set can be used to understand how deck‐mounted seismometers can be used in future landed missions to Mars, Europa, and other planetary bodies. While operating on deck, the SP seismometer showed signals comparable to the Viking‐2 seismometer near 3 Hz where the sensitivity of the Viking instrument peaked. Wind sensitivity showed similar patterns to the Viking instrument, although amplitudes on InSight were ∼80% larger for a given wind velocity. However, during the low‐wind evening hours, the instrument noise levels at frequencies between 0.1 and 1 Hz were comparable to quiet stations on Earth, although deployment to the surface below the Wind and Thermal Shield lowered installation noise by roughly 40 dB in acceleration power. With the observed noise levels and estimated seismicity rates for Mars, detection probability for quakes for a deck‐mounted instrument is low enough that up to years of on‐deck recordings may be necessary to observe an event. Because the noise is dominated by wind acting on the lander, though, deck‐mounted seismometers may be more practical for deployment on airless bodies, and it is important to evaluate the seismicity of the target body and the specific design of the lander. Detection probabilities for operation on Europa reach over 99% for some proposed seismicity models for a similar duration of operation if noise levels are comparable to low‐wind time periods on Mars. Plain Language Summary: In the Viking‐2 mission in the late 1970s, a seismometer was used on the deck of the lander but only saw one event that could be interpreted as a signal like earthquakes on Earth. Because of this, the InSight mission put their seismic instrument on the ground and covered it up to keep the wind from blowing on it. But we can use the time period where it was turned on before getting put on the ground to figure out whether future missions could do seismology without placing it on the ground. We find that the wind blowing on InSight gave us similar signals to the Viking lander, even though InSight had a better instrument. When we use models of how many quakes should be on Mars, we find that keeping the instrument on deck makes it hard to see any quakes unless we listen for months or years. But we may be able to do better on planets and moons that do not have air and wind. A lander on Jupiter's moon Europa, for example, could have a large chance of detecting events within a few days of recording even if the instrument is not put on the ground. Key Points: Based on InSight recordings, atmospheric noise is amplified for seismic sensors on deck, consistent with Viking observations On Mars, this effect suggests long periods of observation (months to years) that are required to detect seismic events On an airless body, like Europa, on‐deck or in‐vault deployment of seismic sensors may be adequate to observe seismic events with days of observation